DFT investigation of pyramidal Au\(_{9}\)M\(^{2+}\) and Au\(_{19}\)M (M = Sc-Ni): similarities and differences of structural evolution, electronic and magnetic properties - Lan, Ngo Thi; Mai, Nguyen Thi; Dang, Nguyen Van; Tung, Nguyen Thanh (Communications in Physics, 2023)
Au102+ and Au20 pyramids, whose stability and inertness are comparable to those of carbon fullerene C60, are considered as important landmarks in the long-history investigation of gold nanoclusters. Numerous experimental and theoretical studies on doping Au102+ and Au20 with transition metal atoms have been carried out for specific properties that can be used as advanced materials in nanotechnology applications. In this work, we discussed the similarities and differences between the structural, stability, and electronic properties of Au9M2+ and Au19M (M = Sc-Ni) clusters using density functional theory calculations. It is found that except for the preferred dopant site, the structural evolution of Au9M2+ cluster resembles that of Au19M in general. Although the V dopant seems to be the important ingredient for the structural transformation in both species, it is remarkable that the transformation appears stronger in Au19V compared with Au9V2+.  The calculated average binding energies are utilized to identify their relative stable patterns. Depending on the 3d transition metal atom dopant, the spin magnetic moments of Au9M2+ and Au19M clusters vary from 0 to 5 μB, reaching the highest value with the Cr-doped species. We show that both Au9Cr2+ and Au19Cr have similarities in the electronic structures and are potential magnetic superatoms.